Assessing the ability to implement ISCM for procurement in construction companies in Iraq (Al-Rasheed state contracting construction company as a case study) (Iraqi Journal of Civil Engineering, 2013)
Constructions industry by their projects and works is regard one of the biggest and important industries in most countries, which most of construction projects needing large amounts of materials, goods and services from different types. It can easily be seen that there is a consistently higher rate for the construction projects in Iraq when compared with the country's other industrial Activities. Integrated supply chain management for procurement processes from planning through good administration to contract closeout give best value from purchasing, storage and delivery just in right amount and time. The objective of this research is to review the concept, definition, and benefits of ISCM for Procurement processes with assessing the implementation of such a procurement world class system for construction companies in Iraq through field survey and developing a "checklist" to investigate, record, weighting, and analyze the facts of existing procurement chain management of Al-Rasheed State contracting construction Company as case study. The research conclusions show that Al-Rasheed CO. implementation percentage of procurement management about 36.3%. where the management isn't aware of procurement management importance, so little knowledge about ISCM and its benefits for procurements processes to company and its projects, , therefore hasn't contrapuntal department for procurement . Several proper solutions were recommended to improve the existing supply chain management for procurement such as establishing procurement department, the role of leadership and commitment to procurement, documentation of ISCM, and proper database for vendors, materials, information and catalogs by modern Information's technology.